2016
DOI: 10.14742/ajet.2640
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the affordances of WeChat for facilitating teaching, social and cognitive presence in semi-synchronous language exchange

Abstract: <p><span>This research is an exploratory study that evaluates the affordances of WeChat for the development of a community of inquiry (CoI) in semi-synchronous language exchange supported by WeChat.</span><span>WeChat is an instant messenger that facilitates a multimodal environment in which interaction can happen synchronously, semi-synchronously and asynchronously through text, audio, video conferencing and a variety of pedagogically facilitating affordances. Differing from most exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 30 publications
(36 reference statements)
1
61
1
1
Order By: Relevance
“…Ninety-one percent of Taiwanese between 12 and 65 years of age used LINE in the first half-year of 2016 (Yeh, 2017). Due to the personal and portable nature incorporated into learning, the Mobile Instant Messaging (MIM) app may have the potential to be employed as a compelling learning tool in higher education (Hsieh & Wu, 2013;Rambe & Bere, 2013;Van de Bogart & Wichadee, 2015;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Ninety-one percent of Taiwanese between 12 and 65 years of age used LINE in the first half-year of 2016 (Yeh, 2017). Due to the personal and portable nature incorporated into learning, the Mobile Instant Messaging (MIM) app may have the potential to be employed as a compelling learning tool in higher education (Hsieh & Wu, 2013;Rambe & Bere, 2013;Van de Bogart & Wichadee, 2015;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…By 2017, there had been over 938 million active users of WeChat in mainland China and overseas (Wikipedia 2017). Wang et al (2016) have explained the rationale in employing WeChat in a foreign language curriculum:…”
Section: Review Of Studies Using Wechat For Language Teachingmentioning
confidence: 99%
“…Related to MIM use, studies have shown that it is easier to demonstrate social presence on MIM platforms compared to other forms of online communication, such as asynchronous online discussion forums (Tang & Hew, 2017). Two possible reasons were provided by previous studies: the easy expression of emotions with emotional icons in MIM applications Wang, Fang, Han and Chen (2016), and the possibility of immediate responses afforded by the notification function.…”
Section: Mobile Instant Messaging In Educationmentioning
confidence: 99%
“…By far, only one study (Wang et al 2016) examined the cognitive presence in the learning process, when knowledge was communicated and constructed together among students. Wang et al (2016) discussed two characteristics of MIM-enabled cognitive presence: easy to reach resolution and effective negotiation of meanings, facilitated by the availability of both audio and text chats. This study discussed all three dimensions of CoI, namely the teaching, social and cognitive presence in language learning.…”
Section: Mobile Instant Messaging In Educationmentioning
confidence: 99%
See 1 more Smart Citation